Proceedings of the 14th International Workshop on Spallation Materials Technology 2020
DOI: 10.7566/jpscp.28.081003
|View full text |Cite
|
Sign up to set email alerts
|

Recent Status of the Pulsed Spallation Neutron Source at J-PARC

Abstract: At the Japan Proton Accelerator Research Complex (J-PARC), the pulsed spallation neutron source has been in operation with a redesigned mercury target vessel from October 2017 to July 2018, during which the operational beam power was restored to 500 kW and the operation with a 1-MW equivalent beam was demonstrated for one hour. The target vessel includes a gas-micro-bubbles injector and a 2-mm-wide narrow mercury flow channel at the front end as measures to suppress the cavitation damage. After the operating p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…It was confirmed for the mercury target vessel that the injection of gas microbubbles is effective in reducing pressure waves at 1 MW. The temperatures of the mercury and target vessel were well within with the designed values [9].…”
Section: Introductionsupporting
confidence: 63%
“…It was confirmed for the mercury target vessel that the injection of gas microbubbles is effective in reducing pressure waves at 1 MW. The temperatures of the mercury and target vessel were well within with the designed values [9].…”
Section: Introductionsupporting
confidence: 63%
“…After finishing the service operation, a 1 MW beam operation at 25 Hz was performed for one hour to confirm the integrity of the facility at the rated beam power of J-PARC. For the mercury target vessel, it was confirmed that the gas microbubbles injection was effective in reducing pressure waves at 1 MW [10].…”
Section: Targets No 2 and No 8 Operationmentioning
confidence: 88%
“…It took seventeen months since the redesigning the structure was started. In the about eight months of service operation, the beam power was ramped up to 500 kW [8]. After finishing the beam operation for the user program, this vessel achieved the operation under the maximum beam power of 1 MW for about 1 hour.…”
Section: Completion Of Beam Operation For Mercury Target Vessel #8mentioning
confidence: 99%